An econometric model of land prices in England - Francis, Frank Noble (2004)
A thesis presented on the land market in England between 1951 and 2001, determining an econometric VAR model of land prices that establishes a link between the price of agricultural land in England and variables that are under the influence of policy makers. The model makes use of the Johansen technique to determine the short run and long run effects of variables that control land prices.